Rare earth cobalt permanent magnet, manufacturing method of rare earth cobalt permanent magnet, and device
Patent Information
- Application Number
- JP2023140900
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-08-31
AI Technical Summary
【0011】 本開示により、磁気特性、特に保磁力及び角形性に優れた希土類コバルト永久磁石、希土類コバルト永久磁石の製造方法、及びデバイスを提供することができる。
Smart Images

Figure 2025034499000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to rare earth cobalt permanent magnets, methods of making rare earth cobalt permanent magnets, and devices. [Background technology]
[0002] Rare earth cobalt permanent magnets such as samarium cobalt magnets are known as one type of permanent magnet. From various standpoints, such as improving magnetic properties, rare earth cobalt permanent magnets with added elements such as Fe, Cu, and Zr are being considered.
[0003] For example, Patent Document 1 discloses a method for producing a ferromagnetic alloy having specific amounts of rare earth elements, Fe, Cu, Co, Zr, Ti, and Hf, and Th 2 Zinc 17 The present invention discloses a permanent magnet having a structure including crystal grains made of a main phase including a type crystal phase and crystal boundaries of the crystal grains, the average grain size of the crystal grains being 50 to 100 μm.
[0004] Patent Document 2 describes a method for producing a ferromagnetic alloy containing specific amounts of rare earth elements, Fe, Cu, Co, Zr, Ti, and Hf, and containing Th 2 Zinc 17 A specific permanent magnet is disclosed that includes a cell phase having a Cu-type crystal phase and a Cu-rich phase having a higher Cu concentration than the cell phase, and the average diameter of the cell phase is 220 nm or less.
[0005] Patent Document 3 also describes a method for producing a ferromagnetic alloy containing specific amounts of rare earth elements R, Fe, Cu, Co, and Zr, and containing Th 2 Zinc 17 A cell phase having a crystalline phase and RCo surrounding the cell phase. 5 A rare earth-cobalt permanent magnet is disclosed that has cell walls containing a crystalline phase of a type structure, and the concentration of the rare earth element in the cell walls is at least 25 at % higher than the concentration of the rare earth element in the cell phase. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2017-168827 A [Patent Document 2] International Publication No. 2015 / 140829 [Patent Document 3] JP 2020-188140 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present disclosure is to provide a rare earth-cobalt permanent magnet having excellent magnetic properties, in particular excellent coercive force and squareness, a method for producing the rare earth-cobalt permanent magnet, and a device. [Means for solving the problem]
[0008] A rare earth cobalt permanent magnet according to one embodiment of the present disclosure is a sintered body having a composition containing 24 to 27 wt% R (where R is the total of rare earth elements including at least Sm), 23 to 27 wt% Fe, 4.0 to 5.0 wt% Cu, 1.5 to 2.5 wt% Zr, 0.1 to 2.5 wt% Mn, with the balance being Co and unavoidable impurities, the magnet having a plurality of crystal grains and a grain boundary phase, the average Mn concentration in the grain boundary phase being 0.5 to 1.5 times the average Mn concentration in the crystal grains, and the crystal grains being composed of Th. 2 Zinc 17 2-17 phase with type structure and RCo 5 The average Mn concentration in the 1-5 phase is 0.4 to 1.5 times the average Mn concentration in the 2-17 phase.
[0009] A device according to one aspect of the present disclosure is a device having the rare earth cobalt permanent magnet described above.
[0010] The method for manufacturing a rare earth cobalt permanent magnet according to one aspect of the present disclosure includes, after sintering, R: 24 to 27 wt% (where R is the total of rare earth elements including at least Sm), Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5 to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and the balance consists of Co and unavoidable impurities. A step (I) of preparing an ingot containing each raw material, a pulverization step (II) of pulverizing the ingot into powder, a pressure molding step (III) of forming the powder into a molded body, a sintering step (IV) of heating the molded body to form a sintered body, a solution treatment step (V) of heating the sintered body to perform solution treatment, a quenching step (VI) of rapidly cooling the sintered body after the solution treatment step (V), and Th 2 Zn 17 2-17 phase of the type structure and RCo 5 An aging treatment step (VII) of forming a 1-5 phase of the type structure is provided. The step (I) of preparing the ingot includes a first ingot heat treatment step of treating the mixture of each raw material at a first ingot heat treatment temperature, and a second ingot heat treatment step of treating the mixture at a second ingot heat treatment temperature after the first ingot heat treatment step. When the sintering temperature of the molded body is S1 and the temperature of the solution treatment is S2, the first ingot heat treatment temperature T1 satisfies S1 - 50 ≤ T1 ≤ S1 (however, when the temperature difference between S1 and S2 is within 50 °C, S2 < T1 ≤ S1), and the second ingot heat treatment temperature T2 satisfies S2 - 30 ≤ T2 ≤ S2.
Advantages of the Invention
[0011] According to the present disclosure, it is possible to provide a rare earth cobalt permanent magnet excellent in magnetic properties, particularly coercivity and rectangularity, a method for manufacturing a rare earth cobalt permanent magnet, and a device.
Brief Description of the Drawings
[0012] [Figure 1] It is a schematic diagram showing an example of a cross section of a rare earth cobalt permanent magnet according to an embodiment. [Diagram 2] It is a schematic diagram showing an enlarged view of part A (a part of crystal grains) in FIG. 1. [Diagram 3] 1 is an electron microscope photograph of a rare earth-cobalt permanent magnet according to an embodiment. [Figure 4] 4 is a graph showing the composition analysis results of the rare earth-cobalt permanent magnet according to the embodiment. [Diagram 5] 1 is an electron microscope photograph of a rare earth-cobalt permanent magnet according to an embodiment. [Figure 6] 4 is a graph showing the composition analysis results of the rare earth-cobalt permanent magnet according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment will be described with reference to the drawings. In addition, unless otherwise specified, the symbol "~" indicating a numerical range includes the lower limit and the upper limit.
[0014] <Rare earth cobalt permanent magnet> The rare earth cobalt permanent magnet according to the present embodiment (hereinafter also referred to as the present permanent magnet) is a sintered body having a composition containing 24 to 27 wt% R (where R is the total of rare earth elements including at least Sm), 23 to 27 wt% Fe, 4.0 to 5.0 wt% Cu, 1.5 to 2.5 wt% Zr, 0.1 to 2.5 wt% Mn, with the balance being Co and unavoidable impurities, and has a plurality of crystal grains and a grain boundary phase, the average Mn concentration in the grain boundary phase is 0.5 to 1.5 times the average Mn concentration in the crystal grains, and the crystal grains are formed of Th. 2 Zinc 17 2-17 phase with type structure and RCo 5 The average Mn concentration in the 1-5 phase is 0.4 to 1.5 times the average Mn concentration in the 2-17 phase.
[0015] In the present embodiment, the rare earth element R is a general term for Sc, Y, and lanthanoids (elements with atomic numbers 57 to 71), and includes at least Sm as the rare earth element R. The rare earth element R may be Sm alone, or may be a combination of Sm and one or more other rare earth elements. As the other rare earth elements, Pr, Nd, Ce, and La are preferable from the viewpoint of magnetic properties. Also, from the viewpoint of magnetic properties, Sm is preferably 80 wt% or more, more preferably 90 wt% or more, and even more preferably 95 wt% or more, based on the total rare earth elements R. In the present permanent magnet, the rare earth element R is contained in an amount of 24 to 27 wt%, preferably 24 to 26 wt%. By containing the rare earth element R in the above ratio, a permanent magnet having high magnetic anisotropy and high coercive force can be obtained.
[0016] The permanent magnet contains 23 to 27 wt%, preferably 23 to 26.5 wt%, of Fe. By containing 23 wt% or more of Fe, the saturation magnetization is improved. Furthermore, by keeping the Fe content at 27 wt% or less, the permanent magnet has high coercive force.
[0017] The permanent magnet contains 4.0 to 5.0 wt%, preferably 4.0 to 4.7 wt%, of Cu. By containing 4.0 wt% or more of Cu, the permanent magnet has high coercive force. Furthermore, by keeping the Cu content at 5.0 wt% or less, the decrease in magnetization is suppressed.
[0018] The permanent magnet contains 0.1 to 2.5 wt% Mn, preferably 0.15 to 1.5 wt%. By containing 0.1 wt% or more Mn, the Cu concentration in the grain boundary phase can be increased. Furthermore, by containing Mn in the above range, it becomes easier to obtain a crystal structure having crystal grains with a relatively large grain size and uniform grain size, improving the squareness ratio. On the other hand, if the Mn content exceeds 2.5 wt%, there is a tendency for the grain size to become smaller.
[0019] It is presumed that the inclusion of 0.1 wt% or more of Mn lowers the melting point, and a large amount of liquid phase appears during sintering, resulting in a concentration distribution in Cu, etc. It is also presumed that the large amount of liquid phase increases the grain size of the crystal grains. It is also presumed that Mn contributes to the demagnetization of the grain boundary phase, suppressing the generation of reverse magnetic domains in the grain boundary phase.
[0020] The permanent magnet contains 1.5 to 2.5 wt%, and preferably 1.9 to 2.3 wt%, of Zr. By containing 1.5 to 2.5 wt% Zr, a permanent magnet with a high maximum energy product (BH)m, which is the maximum magnetostatic energy that a magnet can hold, can be obtained.
[0021] The remainder of the permanent magnet is composed of Co and inevitable impurities. The inclusion of Co improves the thermal stability of the permanent magnet. On the other hand, if the content of Co becomes excessive, the content of Fe decreases relatively. The inevitable impurities are elements that are inevitably mixed in from the raw materials or manufacturing process, and specific examples include, but are not limited to, C, N, P, S, Al, Ti, Cr, Ni, Hf, Sn, and W. In the permanent magnet, the content of inevitable impurities is preferably 5 wt% or less in total, more preferably 1 wt% or less, and even more preferably 0.1 wt% or less, based on the total amount of the permanent magnet. The local content of each element in the permanent magnet can be measured, for example, using energy dispersive X-ray spectrometry (EDX).
[0022] The metallographic structure of the permanent magnet will be described with reference to Figures 1 and 2. Figure 1 is a schematic diagram showing an example of a cross section of a rare earth cobalt permanent magnet according to the present embodiment, and Figure 2 is a schematic diagram showing an enlarged view of part A (a part of crystal grains 10) in Figure 1. As shown in the example of Figure 1, the rare earth cobalt permanent magnet 100 according to the present embodiment has a plurality of crystal grains 10 and a grain boundary phase 20 present between the crystal grains 10. Also, as shown in the example of Figure 2, the crystal grains 10 are composed of Th 2 Zinc 17 Phase 11 with the 2-17 type structure (hereinafter sometimes referred to as phase 11) and RCo5 The crystal grains 10 have a structure (hereinafter, sometimes referred to as a cell structure) in which the 2-17 phase is the main phase (volume ratio of which is 50% or more). 7 It may have a crystal phase of a type structure (hereinafter, sometimes referred to as 1-7 phase) (not shown).
[0023] Th 2 Zinc 17 The phase 11 of the RCo type structure has a crystal structure having an R-3m type space group, and in the present permanent magnet, the Th sites are usually occupied by rare earth elements and Zr, and the Zn sites are usually occupied by Co, Cu, Fe, and Zr. 5 In the phase 12 of the TbCu type structure, the R site is usually occupied by rare earth elements and Zr, and the Co site is usually occupied by Co, Cu, and Fe. 7 In the crystal phase of the type structure, the Tb site is usually occupied by rare earth elements and Zr, and the Cu site is occupied by Co, Cu, and Fe. The crystal structure can be determined by X-ray diffraction.
[0024] As described above, in this permanent magnet, the average Mn concentration in the grain boundary phase 20 is 0.5 to 1.5 times the average Mn concentration in the crystal grains 10. Also, the average Mn concentration in the 1-5 phase 12 is 0.4 to 1.5 times the average Mn concentration in the 2-17 phase 11. Therefore, it is possible to obtain a rare earth cobalt permanent magnet with excellent magnetic properties, particularly excellent coercivity and squareness.
[0025] In the present permanent magnet, the average Mn concentration in the grain boundary phase 20 is preferably 0.8 to 1.2 times the average Mn concentration in the crystal grains 10. The average Cu and Zr concentrations in the grain boundary phase 20 may be at least two times, preferably at least four times, higher than the average Cu and Zr concentrations in the crystal grains 10. The average Mn concentration in the 1-5 phase 12 is preferably 0.8 to 1.0 times the average Mn concentration in the 2-17 phase 11. In this embodiment, by setting each value in such a range, a rare earth cobalt permanent magnet with even better magnetic properties can be obtained.
[0026] Fig. 3 is an electron microscope photograph of the rare earth-cobalt permanent magnet according to this embodiment, showing crystal grains 10 and grain boundary phase 20. Fig. 4 is a graph showing the composition analysis results of the rare earth-cobalt permanent magnet according to this embodiment, showing the composition analysis results in the vicinity of crystal grains 10 and grain boundary phase 20. In other words, the graph shown in Fig. 4 is the composition analysis results starting from crystal grain 10, passing through grain boundary phase 20, and ending at another crystal grain 10.
[0027] As shown in the electron microscope photograph of FIG. 3, a grain boundary phase 20 exists between the crystal grains 10. As shown in the composition analysis results of FIG. 4, the composition of each element in the grain boundary phase 20 varies compared to the composition of each element in the crystal grains 10. Specifically, the amount of Fe and Co in the grain boundary phase 20 is decreased compared to the crystal grains 10, and the amount of Cu and Zr is increased. In addition, in this embodiment, the average concentration of Cu and Zr in the grain boundary phase 20 is preferably two or more times higher than the average concentration of Cu and Zr in the crystal grains 10, and more preferably four or more times higher. In addition, the average Mn concentration in the grain boundary phase 20 is preferably 0.5 to 1.5 times higher than the average Mn concentration in the crystal grains 10, and more preferably 0.8 to 1.2 times higher. That is, in this embodiment, Mn is more uniformly dispersed in the crystal grains 10 and the grain boundary phase 20 compared to Cu and Zr.
[0028] Fig. 5 is an electron microscope photograph of the rare earth-cobalt permanent magnet according to this embodiment, showing the 2-17 phase 11 and the 1-5 phase 12 in the crystal grains. Fig. 6 is a graph showing the composition analysis results of the rare earth-cobalt permanent magnet according to this embodiment, showing the composition analysis results of the 2-17 phase 11 and the 1-5 phase 12. In other words, the graph shown in Fig. 6 is the composition analysis result starting from the 2-17 phase 11, passing through the 1-5 phase 12, and ending at another 2-17 phase 11.
[0029] As shown in the electron microscope photograph of FIG. 5, the crystal grains have a 2-17 phase 11 and a 1-5 phase 12. As shown in the composition analysis results of FIG. 6, the composition of each element in the 1-5 phase 12 varies compared to the composition of each element in the 2-17 phase 11. Specifically, the amounts of Fe, Co, and Zr in the 1-5 phase 12 are decreased compared to the 2-17 phase 11, and the amounts of Cu and Sm are increased. In this embodiment, the average Mn concentration in the 1-5 phase 12 is preferably 0.4 to 1.5 times, and more preferably 0.8 to 1.0 times, the average Mn concentration in the 2-17 phase 11. That is, in this embodiment, Mn is dispersed more uniformly in the crystal grains than Cu and Zr. In other words, Mn is dispersed more uniformly in the 2-17 phase 11 and the 1-5 phase 12 compared to Cu and Zr.
[0030] In this embodiment, the "average concentration" of each element is the arithmetic mean concentration at the analysis point in each phase.
[0031] The electron microscope photographs and composition analysis results shown in Figures 3 to 6 can be measured using the following method. First, the sample is physically polished with waterproof abrasive paper or the like. Then, the surface is processed using a focused ion beam (FIB) or ion milling so that no unevenness is formed on the surface. The target area of the processed sample is observed using a transmission electron microscope (TEM). The observation magnification should be 3000 to 5000 times for the grain boundary phase and 10000 to 30000 times for the cell structure within the crystal grains. In addition, the composition of the observed area is directly analyzed using energy dispersive X-ray spectroscopy (EDX). The composition analysis should be performed at 5 to 20 nm for the grain boundary phase and 0.5 to 2.0 nm for the cell structure.
[0032] This permanent magnet has a sintered density of 8.20 to 8.45 g / cm 3 is preferable, and 8.25 to 8.40 g / cm 3By setting the sintered body density in this range, the residual magnetic flux density (Br) and the squareness ratio can be particularly improved.
[0033] The permanent magnet is characterized by the fact that its structure is homogenized through heat treatments such as sintering, solution treatment, and subsequent quenching, and that its permanent magnetic properties are manifested through further aging.
[0034] The permanent magnet has a residual magnetic flux density (Br) of 11.8 kG or more, preferably 12.0 kG or more. The coercive force (Hcj) is 20 kOe or more, preferably 22 kOe or more. The maximum energy product (BH)m is 260 kJ / m. 3 More than 265 kJ / m 3 Here, the maximum energy product (BH)m is the maximum magnetostatic energy that a magnetic body can hold, and represents the maximum value of the product of the magnetic flux density B and the magnetic field H on the BH decay curve in the second quadrant (decay curve) of the magnetization curve (BH curve).
[0035] The squareness ratio of this permanent magnet, which is the ratio (Hk / Hcj) of the magnetic field (Hk) to the coercive force (Hcj), is 65% or more, and preferably 70% or more. Here, the magnetic field (Hk) is defined as the magnetic field at 90% magnetization of the residual magnetization.
[0036] It is believed that the coercive force of this permanent magnet is generated by the pinning of the magnetic domain walls between the 2-17 and 1-5 phases during magnetic domain wall motion. In addition, Fe and Cu are concentrated in the 2-17 and 1-5 phases, respectively, during phase separation, improving the squareness ratio and increasing the maximum energy product (BH)m. Furthermore, the more constant the composition ratio of the 2-17 and 1-5 phases is throughout the sample, the better the magnetic properties can be obtained.
[0037] When measuring magnetic properties, first process the sample into the specified shape. When using a DC BH tracer, magnetize it by applying a magnetic field about 3 to 4 times higher than the predicted Hcj, and then measure according to the device's operating instructions. When using a pulsed BH tracer, magnetization is not necessary.
[0038] <Method for manufacturing rare earth cobalt permanent magnet> Next, a method for manufacturing a rare earth cobalt permanent magnet according to the present embodiment will be described. The manufacturing method of this permanent magnet is such that after sintering, it contains R: 24 to 27 wt% (where R is the total of rare earth elements including at least Sm), Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5 to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and the balance is composed of Co and unavoidable impurities. A step (I) of preparing an ingot containing each raw material, a pulverizing step (II) of making the ingot into powder, a pressure molding step (III) of making the powder into a molded body, a sintering step (IV) of heating the molded body to form a sintered body, a solution treatment step (V) of heating the sintered body to perform solution treatment, a quenching step (VI) of rapidly cooling the sintered body after the solution treatment step (V), Th 2 Zn 17 2-17 phase of the type structure and RCo 5 An aging treatment step (VII) of forming a 1-5 phase of the type structure is provided. The step (I) of preparing the ingot includes a first ingot heat treatment step of treating the mixture of the respective raw materials at a first ingot heat treatment temperature, and a second ingot heat treatment step of treating the mixture at a second ingot heat treatment temperature after the first ingot heat treatment step. When the sintering temperature of the molded body is S1 and the temperature of the solution treatment is S2, the first ingot heat treatment temperature T1 satisfies S1 - 50 ≤ T1 ≤ S1 (however, when the temperature difference between S1 and S2 is within 50 °C, S2 < T1 ≤ S1), and the second ingot heat treatment temperature T2 satisfies S2 - 30 ≤ T2 ≤ S2.
[0039] Hereinafter, the manufacturing method of this permanent magnet will be described in detail.
[0040] In step (I) of preparing an ingot containing each raw material, the raw materials are Sm as a base, rare earth elements such as Nd, Pr, Ce, Fe, Cu, Co, and further a mother alloy such as FeZr or CuZr. Here, it is preferable to select a mother alloy with a composition having a low eutectic temperature, since this makes it easier to homogenize the composition of the alloy ingot, and for example, FeZr or CuZr is preferable. In the case of FeZr, a weight ratio of about Fe80%Zr20%, and in the case of CuZr, a weight ratio of Cu50%Zr50% are suitable for this embodiment. These raw materials are mixed to obtain a predetermined composition, placed in a crucible such as alumina, and 1×10 -2 The alloy is melted in a high-frequency melting furnace in a vacuum of less than torr or in an inert gas atmosphere, and then cast into a mold to obtain an alloy ingot.
[0041] Considering the manufacturing cost, it is better to use the obtained alloy ingot as it is, but in this embodiment, heat treatment is performed to make the structure more uniform and improve the magnetic properties. Specifically, in order to eliminate and homogenize the phases formed during casting, a first ingot heat treatment step is performed at a first ingot heat treatment temperature, and a second ingot heat treatment step is performed at a second ingot heat treatment temperature.
[0042] In the first ingot heat treatment step, from the viewpoint of suppressing the evaporation of Sm, the first ingot heat treatment temperature is preferably lower than the sintering temperature and 50°C higher than the solutionizing temperature. However, when the difference between the sintering temperature and the solutionizing temperature is within 50°C, the first ingot heat treatment temperature is preferably equal to or lower than the sintering temperature and higher than the solutionizing temperature. Specifically, when the sintering temperature of the compact is S1 and the temperature of the solutionizing treatment (solutionizing temperature) is S2, the first ingot heat treatment temperature T1 is preferably set so as to satisfy S1 - 50 ≤ T1 ≤ S1 (however, when the temperature difference between S1 and S2 is within 50°C, S2 < T1 ≤ S1). Also, in the present embodiment, the first ingot heat treatment temperature T1 is more preferably set so as to satisfy S1 - 30 ≤ T1 ≤ S1 (however, when the temperature difference between S1 and S2 is within 30°C, S2 < T1 ≤ S1). The heat treatment time in the first ingot heat treatment step is preferably 0.5 to 3 hours, and more preferably 1 to 2 hours. By setting the heat treatment temperature and the heat treatment time within this range, it is possible to suppress the evaporation of Sm and eliminate the dendrite phase and other unintended phases.
[0043] Also, in the second ingot heat treatment step, from the viewpoint of promoting homogenization, the second ingot heat treatment temperature is preferably equal to or lower than the solutionizing temperature and higher than a temperature 30 degrees lower than the solutionizing temperature. Specifically, the second ingot heat treatment temperature T2 is preferably set so as to satisfy S2 - 30 ≤ T2 ≤ S2. Also, in the present embodiment, the second ingot heat treatment temperature T2 is more preferably set so as to satisfy S2 - 20 ≤ T2 ≤ S2. The heat treatment time in the second ingot heat treatment step is preferably 1 to 10 hours, and more preferably 3 to 8 hours. By setting the heat treatment time within this range, it is possible to suppress the evaporation of Sm and homogenize the structure.
[0044] When the temperature is changed from the first ingot heat treatment temperature T1 to the second ingot heat treatment temperature T2, the temperature is preferably decreased at a rate of 0.1 to 20°C / min, more preferably at a rate of 1 to 10°C / min, from the viewpoint of suppressing evaporation of Sm and promoting homogenization. In this embodiment, the ingot heat treatment process is not limited to two stages, and the ingot heat treatment process may be three or more stages. Also, instead of casting into a metal mold, a method called strip casting may be used in which molten metal is dropped onto a copper roll to obtain a flake-shaped alloy with a thickness of about 1 mm.
[0045] Next, the ingot prepared as described above is pulverized to obtain a powder (pulverization step (II)). First, the ingot is coarsely pulverized to obtain a powder having an average size of about 100 to 500 μm. Then, this coarsely pulverized powder is finely pulverized by a ball mill, a jet mill, or the like to obtain a powder having an average size of about 1 μm to 10 μm. By obtaining such an average particle size, it is possible to shorten the sintering time in the sintering step described later, and also to manufacture a uniform permanent magnet. Furthermore, in this embodiment, in terms of improving sinterability, it is preferable that the particle size distribution of the finely pulverized powder is such that D10, which is the particle size value of 10% or less of the total, is less than 4 μm, the median diameter D50 (particle size value of 50% or less of the total) is 5 to 8 μm, and D90, which is the particle size value of 90% or less of the total, is less than 16 μm. It is more preferable that D10 is less than 3 μm, D50 is 5 to 7 μm, and D90 is less than 15 μm. By obtaining such a particle size distribution, it is possible to obtain a powder having an average size of 8.20 g / cm 3 It is possible to obtain a sintered body having a density equal to or higher than this.
[0046] Next, the powder obtained as described above is pressure molded to produce a molded body (pressure molding step (III)). In this embodiment, pressure molding is preferably performed in a constant magnetic field in order to align the crystal orientation of the powder and improve the magnetic properties. The relationship between the direction of the magnetic field and the pressing direction is not particularly limited and may be selected appropriately depending on the shape of the product, etc. For example, when manufacturing a ring magnet or a thin plate magnet, a parallel magnetic field press can be used in which a magnetic field is applied parallel to the pressing direction. On the other hand, in order to achieve excellent magnetic properties, a perpendicular magnetic field press in which a magnetic field is applied perpendicular to the pressing direction is preferable.
[0047] The strength of the magnetic field is not particularly limited, and may be, for example, 15 kOe or less or 15 kOe or more depending on the application of the product. In particular, from the viewpoint of excellent magnetic properties, it is preferable to perform pressure molding in a magnetic field of 15 kOe or more. The pressure during pressure molding may be appropriately adjusted depending on the size, shape, etc. of the product. For example, it may be 0.5 to 2.0 ton / cm. 2 The pressure can be.
[0048] Next, the molded body obtained as described above is heated to form a sintered body (sintering step (IV)). In this embodiment, the sintering conditions may be known conditions as long as the sintered body is sufficiently densified. From the viewpoint of densifying the sintered body, the sintering temperature is preferably 1170 to 1215°C, more preferably 1180 to 1210°C. By setting the sintering temperature at 1215°C or less, evaporation of rare earth elements, particularly Sm, is suppressed, and a permanent magnet with excellent magnetic properties can be produced. In this embodiment, since the melting point tends to decrease due to the presence of Mn, sufficient sintering is possible at 1215°C or less.
[0049] Regarding the temperature rise conditions in the sintering step, from the viewpoint of removing the adsorbed gas contained in the compact, it is preferable to start evacuation at room temperature and raise the temperature at 1 to 10°C / min. During the temperature rise process, a hydrogen atmosphere may be used instead of evacuation. In this case, it is also preferable to switch to a vacuum atmosphere in the range of 1150°C or less. The sintering time is preferably 20 to 210 minutes, more preferably 30 to 150 minutes, from the viewpoint of sufficiently densifying while suppressing the evaporation of Sm. Furthermore, from the viewpoint of suppressing oxidation, the sintering step is preferably performed in a vacuum of 1000 Pa or less or in an inert gas atmosphere, and further, from the viewpoint of increasing the density of the sintered body, it is more preferable to perform the sintering step in a vacuum of 100 Pa or less.
[0050] Next, the sintered body is heated and subjected to solution treatment (solution treatment step (V)). The solution treatment is carried out to separate the 1-7 phase (TbCu 7 It is a process for forming a mold structure). From the viewpoint of the production process, it is preferable to carry out the solution treatment without cooling to room temperature after sintering. Here, when moving from the sintering temperature to the solution treatment temperature, from the viewpoint of suppressing the evaporation of Sm and promoting homogenization, it is preferable to lower the temperature at a rate of 0.1 to 10 ° C / min, and more preferably at a rate of 0.2 to 2.5 ° C / min. The solution treatment is carried out at a temperature of 1110 to 1165 ° C in a vacuum of 1000 Pa or less or in an inert atmosphere. Since the optimal solution treatment temperature varies depending on the composition, it is preferable to carry out the solution treatment at a temperature suitable for each composition. If the solution treatment temperature is too high, the liquid phase remains and homogenization cannot be performed, and if it is too low, homogenization takes a long time, so the solution treatment temperature is preferably 1120 to 1160 ° C. The solution treatment time is preferably 5 to 150 hours, more preferably 10 to 100 hours. If the solution treatment time is too short, homogenization into the 1-7 phase becomes insufficient, whereas if the solution treatment time is too long, Sm evaporates and good magnetic properties cannot be obtained, so it is preferable that the solution treatment time is within the above range.
[0051] Next, the sintered body is quenched after the solution treatment (quenching step (VI)). Quenching is a process for maintaining the 1-7 phase obtained by the solution treatment, and if quenching is insufficient, the structure will change during cooling. The temperature range that is particularly important for effective quenching is from the solution temperature to 600°C. In order to maintain the 1-7 phase, a quenching rate of 60°C / min or more is necessary within the above range, and a quenching rate of 80°C / min or more is preferable.
[0052] Next, the compact after the quenching step is aged to form the 2-17 phase and the 1-5 phase (aging step (VII)). The aging temperature is not particularly limited, but in order to obtain a permanent magnet having the 2-17 phase as the main phase and the 2-17 phase and the 1-5 phase homogeneously, it is preferable to hold the temperature at 700 to 900°C for 2 to 20 hours, and then cool the magnet to at least 400°C at a cooling rate of 2°C / min or less. By holding the temperature at 700°C to 900°C for 2 to 20 hours, the 2-17 phase and the 1-5 phase can be homogeneously formed. Among these, it is preferable to perform the aging treatment in a temperature range of 800 to 850°C. In addition, in order to obtain good magnetic properties, it is preferable to set the cooling rate to 2°C / min or less, and more preferably to set it to 0.5°C / min or less.
[0053] By using the method for producing a rare earth-cobalt permanent magnet according to the present embodiment described above, it is possible to produce a rare earth-cobalt permanent magnet having the above-mentioned characteristics. That is, the magnet has a plurality of crystal grains and a grain boundary phase, the average Mn concentration in the grain boundary phase is 0.5 to 1.5 times the average Mn concentration in the crystal grains, and the crystal grains are 2 Zinc 17 2-17 phase with type structure and RCo 5 According to the present invention, it is possible to produce a rare earth cobalt permanent magnet having a 1-5 phase with a 2-17 type structure, in which the average Mn concentration in the 1-5 phase is 0.4 to 1.5 times that in the 2-17 phase.
[0054] <Device> This embodiment can further provide a device having the rare earth cobalt permanent magnet described above. Specific examples of such devices include watches, electric motors, various instruments, communication devices, computer terminals, speakers, video disks, sensors, and the like. Furthermore, the rare earth cobalt permanent magnet according to this embodiment has excellent heat resistance and is less likely to deteriorate in magnetic force even at high environmental temperatures, so it can be suitably used in angle sensors used in the engine rooms of automobiles, ignition coils, drive motors for HEVs (hybrid electric vehicles), and the like. In particular, as described above, it has high residual magnetic flux density, high coercive force, and a high squareness ratio, so it can be suitably applied to variable magnetic field motors, and a variable magnetic field motor that achieves high efficiency from low speed to high speed can be obtained.
[0055] According to the present embodiment described above, it is possible to provide a rare earth-cobalt permanent magnet having excellent magnetic properties, particularly excellent coercive force and squareness, a method for producing the rare earth-cobalt permanent magnet, and a device. EXAMPLES
[0056] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these descriptions.
[0057] (Examples 1 to 3) A mother alloy of Fe20%Zr80% and each raw material were prepared so as to have the composition of Examples 1 to 3 in Table 1-1, and were melted in a high-frequency melting furnace and cast to obtain alloy ingots. Each of the obtained alloy ingots was heat-treated at 1155°C (Example 1), 1180°C (Example 2), and 1205°C (Example 3) for 2 hours, and then heat-treated at 1125°C for 5 hours. Then, each of the heat-treated alloy ingots was coarsely crushed in an inert gas to an average size of about 100 to 500 μm, and then finely crushed in an inert gas using a ball mill to a D10 of about 2.5 μm, a D50 of about 6 μm, and a D90 of about 13.5 μm. These powders were each subjected to a magnetic field of 15 kOe at 1 ton / cm 2A compact was obtained by pressing at a pressure of 100 .mu.m.
[0058] This compact was sintered at 1205°C for 1 hour in a vacuum of less than 1000 Pa, and then solution-treated at 1130°C for 30 hours. It was then quenched from 1000 to 600°C at a cooling rate of 80°C / min. After quenching, it was held at 825°C for 25 hours, and then slowly cooled to 350°C at a cooling rate of 0.5°C / min, and aged to obtain a permanent magnet. In Table 1-1, ΔT1 is the difference between the sintering temperature (S1) and the first ingot heat treatment temperature (T1), ΔT2 is the difference between the solution temperature (S2) and the second ingot heat treatment temperature (T2), and S1-S2 is the difference between the sintering temperature (S1) and the solution temperature (S2). The same applies to the other tables.
[0059] The magnetic properties of this permanent magnet were measured while it was still in the molded state. The magnetic properties of the permanent magnet were measured using a BH tracer. In addition, the permanent magnet was subjected to the necessary processing, and microstructural observation and composition analysis were performed using TEM / EDX. Table 1-2 shows the residual magnetic flux density (Br), coercive force (Hcj), squareness ratio (Hk / Hcj), ratio of grain boundary phase to crystal grains with average Mn concentration, ratio of 1-5 phase to 2-17 phase within crystal grains (within cell structure) with average Mn concentration, ratio of grain boundary phase to crystal grains with average Cu concentration, and ratio of grain boundary phase to crystal grains with average Zr concentration.
[0060] (Comparative Examples 1 to 2) Permanent magnets according to Comparative Examples 1 and 2 were obtained in the same manner as in Examples 1 to 3, except that the first ingot heat treatment temperature (T1) was changed as in Comparative Examples 1 and 2 in Table 1-1.
[0061] [Table 1]
[0062] As shown in Tables 1-1 and 1-2, in Examples 1 to 3, the average Mn concentration in the grain boundary phase was in the range of 0.5 to 1.5 times that of the average Mn concentration in the crystal grains. In addition, in Examples 1 to 3, the average Mn concentration in the 1-5 phase was in the range of 0.4 to 1.2 times that of the average Mn concentration in the 2-17 phase. In addition, in Examples 1 to 3, the average Cu and Zr concentrations in the grain boundary phase were more than twice as high as the average Cu and Zr concentrations in the crystal grains. Therefore, in Examples 1 to 3, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) were good values.
[0063] (Examples 4 to 6) A mother alloy of Fe20%Zr80% and each raw material were prepared so as to have the composition of Examples 4 to 6 in Table 2-1, and were melted in a high-frequency melting furnace and cast to obtain alloy ingots. Each of the obtained alloy ingots was heat-treated at 1170 for 1 hour, and then heat-treated at 1110°C (Example 4), 1125°C (Example 5), and 1140°C (Example 6) for 5 hours. Then, each of the heat-treated alloy ingots was coarsely crushed in an inert gas to an average size of about 100 to 500 μm, and then finely crushed in an inert gas using a ball mill to a D10 of about 2.5 μm, a D50 of about 6 μm, and a D90 of about 13.5 μm. These powders were each subjected to a magnetic field of 15 kOe at 1 ton / cm 2 A compact was obtained by pressing at a pressure of 100 .mu.m.
[0064] This compact was sintered in a vacuum of less than 1000 Pa at 1200°C for 1.5 hours, and then solution-treated at 1140°C for 100 hours. It was then quenched from 1000 to 600°C at a cooling rate of 80°C / min. After quenching, it was held at 825°C for 25 hours, and then slowly cooled to 350°C at a cooling rate of 0.5°C / min, and aged to obtain a permanent magnet.
[0065] The magnetic properties of this permanent magnet were measured while it was still in the molded state. The magnetic properties of the permanent magnet were measured using a BH tracer. In addition, the permanent magnet was subjected to the necessary processing, and microstructural observation and composition analysis were performed using TEM / EDX. The residual magnetic flux density (Br), coercive force (Hcj), squareness ratio (Hk / Hcj), ratio of grain boundary phase to crystal grains with average Mn concentration, ratio of 1-5 phase to 2-17 phase within crystal grains (within cell structure) with average Mn concentration, ratio of grain boundary phase to crystal grains with average Cu concentration, and ratio of grain boundary phase to crystal grains with average Zr concentration of this permanent magnet are shown in Table 2-2.
[0066] (Comparative Examples 3 to 4) Permanent magnets according to Comparative Examples 3 and 4 were obtained in the same manner as in Examples 4 to 6, except that the second ingot heat treatment temperature (T2) was changed as in Comparative Examples 3 and 4 in Table 2-1.
[0067] [Table 2]
[0068] As shown in Tables 2-1 and 2-2, in Examples 4 to 6, the average Mn concentration in the grain boundary phase was in the range of 0.5 to 0.9 times that of the average Mn concentration in the crystal grains. In addition, in Examples 4 to 6, the average Mn concentration in the 1-5 phase was in the range of 0.6 to 0.8 times that of the average Mn concentration in the 2-17 phase. In addition, in Examples 4 to 6, the average Cu and Zr concentrations in the grain boundary phase were more than twice as high as the average Cu and Zr concentrations in the crystal grains. Therefore, in Examples 4 to 6, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) were good values.
[0069] (Examples 7 to 12) A mother alloy of Fe20%Zr80% and each raw material were prepared so as to have the composition of Examples 7 to 12 in Table 3-1, and were melted in a high-frequency melting furnace and cast to obtain alloy ingots. In Example 7, the obtained alloy ingot was heat-treated at 1170°C for 1 hour, and then heat-treated at 1135°C for 6 hours. In Example 8, the obtained alloy ingot was heat-treated at 1170°C for 1 hour, and then heat-treated at 1130°C for 6 hours. In Example 9, the obtained alloy ingot was heat-treated at 1185°C for 1 hour, and then heat-treated at 1135°C for 6 hours. In Example 10, the obtained alloy ingot was heat-treated at 1185°C for 1 hour, and then heat-treated at 1130°C for 6 hours. In Example 11, the obtained alloy ingot was heat-treated at 1210°C for 1 hour, and then heat-treated at 1135°C for 6 hours. In Example 12, the obtained alloy ingot was heat-treated at 1210° C. for 1 hour, and then heat-treated at 1130° C. for 6 hours.
[0070] Each of the heat-treated alloy ingots was coarsely crushed in an inert gas to an average size of about 100 to 500 μm, and then finely crushed in an inert gas using a ball mill to a D10 of about 2.5 μm, a D50 of about 6 μm, and a D90 of about 13.5 μm. These powders were then subjected to a magnetic field of 15 kOe and a strength of 1 ton / cm. 2 A compact was obtained by pressing at a pressure of 100 .mu.m.
[0071] In Examples 7, 9, and 11, the molded body was sintered at 1210°C for 0.5 hours in a vacuum of less than 1000 Pa, and then subjected to solution treatment at 1165°C for 50 hours. In Examples 8, 10, and 12, the molded body was sintered at 1210°C for 0.5 hours in a vacuum of less than 1000 Pa, and then subjected to solution treatment at 1160°C for 50 hours. Then, the molded body was quenched from 1000 to 600°C at a cooling rate of 80°C / min. After quenching, the molded body was held at 825°C for 25 hours, and then slowly cooled to 350°C at a cooling rate of 0.5°C / min, and aged to obtain a permanent magnet.
[0072] The magnetic properties of this permanent magnet were measured while it was still in the molded state. The magnetic properties of the permanent magnet were measured using a BH tracer. In addition, the permanent magnet was subjected to the necessary processing, and microstructural observation and composition analysis were performed using TEM / EDX. The residual magnetic flux density (Br), coercive force (Hcj), squareness ratio (Hk / Hcj), ratio of grain boundary phase to crystal grains with average Mn concentration, ratio of 1-5 phase to 2-17 phase within crystal grains (within cell structure) with average Mn concentration, ratio of grain boundary phase to crystal grains with average Cu concentration, and ratio of grain boundary phase to crystal grains with average Zr concentration of this permanent magnet are shown in Table 3-2.
[0073] (Comparative Examples 5 to 8) Permanent magnets according to Comparative Examples 5 to 8 were obtained in the same manner as in Examples 7 to 12, except that the conditions for the heat treatment of the alloy ingot, the sintering conditions, and the solution treatment conditions were changed as follows.
[0074] In Comparative Example 5, the obtained alloy ingot was heat-treated at 1160°C for 1 hour, and then heat-treated at 1135°C for 6 hours. In Comparative Example 6, the obtained alloy ingot was heat-treated at 1160°C for 1 hour, and then heat-treated at 1130°C for 6 hours. In Comparative Example 7, the obtained alloy ingot was heat-treated at 1215°C for 1 hour, and then heat-treated at 1135°C for 6 hours. In Comparative Example 8, the obtained alloy ingot was heat-treated at 1215°C for 1 hour, and then heat-treated at 1130°C for 6 hours.
[0075] In Comparative Examples 5 and 7, the compacts were sintered in a vacuum of less than 1000 Pa at 1210°C for 1 hour, and then subjected to solution treatment at 1165°C for 6 hours. In Comparative Examples 6 and 8, the compacts were sintered in a vacuum of less than 1000 Pa at 1210°C for 1 hour, and then subjected to solution treatment at 1160°C for 6 hours.
[0076] [Table 3]
[0077] As shown in Tables 3-1 and 3-2, in Examples 7 to 12, the average Mn concentration in the grain boundary phase was in the range of 0.5 to 0.8 times that of the average Mn concentration in the crystal grains. In addition, in Examples 7 to 12, the average Mn concentration in the 1-5 phase was in the range of 0.4 to 0.8 times that of the average Mn concentration in the 2-17 phase. In addition, in Examples 7 to 12, the average Cu and Zr concentrations in the grain boundary phase were more than twice as high as the average Cu and Zr concentrations in the crystal grains. Therefore, in Examples 7 to 12, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) were good values.
[0078] (Examples 13 to 20) A mother alloy of Fe20%Zr80% and each raw material were prepared so as to have the composition of Examples 13 to 20 in Table 4-1, and were melted in a high-frequency melting furnace and cast to obtain alloy ingots. In Example 13, the obtained alloy ingot was heat-treated at 1185°C for 1 hour, and then heat-treated at 1130°C for 6 hours. In Example 14, the obtained alloy ingot was heat-treated at 1160°C for 1 hour, and then heat-treated at 1100°C for 10 hours. In Examples 15 to 16, the obtained alloy ingot was heat-treated at 1180°C for 2 hours, and then heat-treated at 1120°C for 8 hours. In Examples 17 to 18, the obtained alloy ingot was heat-treated at 1175°C for 3 hours, and then heat-treated at 1125°C for 4 hours. In Examples 19 and 20, the obtained alloy ingots were heat-treated at 1195° C. for 1.5 hours, and then heat-treated at 1115° C. for 9 hours.
[0079] Each of the heat-treated alloy ingots was coarsely crushed in an inert gas to an average size of about 100 to 500 μm, and then finely crushed in an inert gas using a ball mill to a D10 of about 2.5 μm, a D50 of about 6 μm, and a D90 of about 13.5 μm. These powders were then subjected to a magnetic field of 15 kOe and a strength of 1 ton / cm. 2 A compact was obtained by pressing at a pressure of 100 .mu.m.
[0080] In Example 13, the molded body was sintered at 1215°C for 1.5 hours in a vacuum of less than 1000 Pa, and then subjected to solution treatment at 1140°C for 30 hours. In Example 14, the molded body was sintered at 1170°C for 2.5 hours in a vacuum of less than 1000 Pa, and then subjected to solution treatment at 1110°C for 40 hours. In Examples 15 and 16, the molded body was sintered at 1185°C for 2.0 hours in a vacuum of less than 1000 Pa, and then subjected to solution treatment at 1125°C for 50 hours. In Examples 17 and 18, the molded body was sintered at 1195°C for 1.0 hour in a vacuum of less than 1000 Pa, and then subjected to solution treatment at 1140°C for 60 hours. In Examples 19 and 20, the molded body was sintered at 1200°C for 1.0 hour in a vacuum of less than 1000 Pa, and then subjected to solution treatment at 1130°C for 50 hours.
[0081] Then, it was quenched from 1000 to 600°C at a cooling rate of 80°C / min. After quenching, it was held at 825°C for 25 hours, and then aged by slowly cooling to 350°C at a cooling rate of 0.5°C / min to obtain a permanent magnet.
[0082] The magnetic properties of this permanent magnet were measured while it was still in the molded state. The magnetic properties of the permanent magnet were measured using a BH tracer. In addition, the permanent magnet was subjected to the necessary processing, and microstructural observation and composition analysis were performed using TEM / EDX. The residual magnetic flux density (Br), coercive force (Hcj), squareness ratio (Hk / Hcj), ratio of grain boundary phase to crystal grains with average Mn concentration, ratio of 1-5 phase to 2-17 phase within crystal grains (within cell structure) with average Mn concentration, ratio of grain boundary phase to crystal grains with average Cu concentration, and ratio of grain boundary phase to crystal grains with average Zr concentration of this permanent magnet are shown in Table 4-2.
[0083] (Comparative Examples 9 to 18) A mother alloy of Fe20%Zr80% and each raw material were prepared so as to have the composition of Comparative Examples 9 to 18 in Table 4-1, and were melted in a high-frequency melting furnace and cast to obtain alloy ingots. In Comparative Examples 9 to 10, the obtained alloy ingots were heat-treated at 1185°C for 1 hour, and then heat-treated at 1130°C for 6 hours. In Comparative Examples 11 to 12, the obtained alloy ingots were heat-treated at 1160°C for 1 hour, and then heat-treated at 1100°C for 10 hours. In Comparative Examples 13 to 14, the obtained alloy ingots were heat-treated at 1180°C for 2 hours, and then heat-treated at 1120°C for 8 hours. In Comparative Examples 15 to 16, the obtained alloy ingots were heat-treated at 1175°C for 3 hours, and then heat-treated at 1125°C for 4 hours. In Comparative Examples 17 and 18, the obtained alloy ingots were heat-treated at 1195° C. for 1.5 hours, and then heat-treated at 1115° C. for 9 hours.
[0084] Each of the heat-treated alloy ingots was coarsely crushed in an inert gas to an average size of about 100 to 500 μm, and then finely crushed in an inert gas using a ball mill to a D10 of about 2.5 μm, a D50 of about 6 μm, and a D90 of about 13.5 μm. These powders were then subjected to a magnetic field of 15 kOe and a strength of 1 ton / cm. 2 A compact was obtained by pressing at a pressure of 100 .mu.m.
[0085] In Comparative Examples 9-10, the molded body was sintered in a vacuum of less than 1000 Pa at 1215°C for 1.5 hours, and then subjected to solution treatment at 1140°C for 30 hours. In Comparative Examples 11-12, the molded body was sintered in a vacuum of less than 1000 Pa at 1170°C for 2.5 hours, and then subjected to solution treatment at 1110°C for 40 hours. In Comparative Examples 13-14, the molded body was sintered in a vacuum of less than 1000 Pa at 1185°C for 2.0 hours, and then subjected to solution treatment at 1125°C for 50 hours. In Comparative Examples 15-16, the molded body was sintered in a vacuum of less than 1000 Pa at 1195°C for 1.0 hour, and then subjected to solution treatment at 1140°C for 60 hours. In Comparative Examples 17-18, the molded body was sintered in a vacuum of less than 1000 Pa at 1200°C for 1.0 hour, and then subjected to solution treatment at 1130°C for 50 hours.
[0086] Then, it was quenched from 1000 to 600°C at a cooling rate of 80°C / min. After quenching, it was held at 825°C for 25 hours, and then aged by slowly cooling to 350°C at a cooling rate of 0.5°C / min to obtain a permanent magnet.
[0087] The magnetic properties of this permanent magnet were measured while it was still in the molded state. The magnetic properties of the permanent magnet were measured using a BH tracer. In addition, the permanent magnet was subjected to the necessary processing, and microstructural observation and composition analysis were performed using TEM / EDX. The residual magnetic flux density (Br), coercive force (Hcj), squareness ratio (Hk / Hcj), ratio of grain boundary phase to crystal grains with average Mn concentration, ratio of 1-5 phase to 2-17 phase within crystal grains (within cell structure) with average Mn concentration, ratio of grain boundary phase to crystal grains with average Cu concentration, and ratio of grain boundary phase to crystal grains with average Zr concentration of this permanent magnet are shown in Table 3-2.
[0088] [Table 4]
[0089] [Table 5]
[0090] As shown in Tables 4-1 and 4-2, in Example 13 and Comparative Examples 9 to 10, the composition of Sm, which is a rare earth element, is changed. From the results of Example 13 and Comparative Examples 9 to 10, when the composition range of Sm is 24 to 27 wt%, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) are good values. In Example 14 and Comparative Examples 11 to 12, the composition of Fe is changed. From the results of Example 14 and Comparative Examples 11 to 12, when the composition range of Fe is 23 to 27 wt%, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) are good values. In Examples 15 to 16 and Comparative Examples 13 to 14, the composition of Cu is changed. From the results of Examples 15 to 16 and Comparative Examples 13 to 14, when the Cu composition was 4.0 to 5.0 wt%, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) were good.
[0091] In Examples 17 to 18 and Comparative Examples 15 to 16, the Zr composition was changed. From the results of Examples 17 to 18 and Comparative Examples 15 to 16, when the Zr composition range was 1.5 to 2.5 wt%, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) were good. In Examples 19 to 20 and Comparative Examples 17 to 18, the Mn composition was changed. From the results of Examples 19 to 20 and Comparative Examples 17 to 18, when the Mn composition range was 0.1 to 2.5 wt%, the residual magnetic flux density (Br), coercive force (Hcj), and squareness ratio (Hk / Hcj) were good.
[0092] As shown in the above Examples 1 to 20, when samples were prepared under the specified conditions, the average Mn concentration in the grain boundary phase was in the range of 0.5 to 1.5 times that of the average Mn concentration in the crystal grains (condition A). The average Mn concentration in the 1-5 phase was in the range of 0.4 to 1.5 times that of the average Mn concentration in the 2-17 phase (condition B). The average Cu and Zr concentrations in the grain boundary phase were more than twice as high as those in the crystal grains (condition C). The residual magnetic flux density (Br) was 11.8 kG or more, the coercive force (Hcj) was 20 kOe, and the squareness ratio (Hk / Hcj) was 65% or more.
[0093] On the other hand, samples in which the heat treatment conditions of the ingot were outside the prescribed range or the compositions were outside the prescribed range (i.e., Comparative Examples 1 to 18) did not satisfy some or all of the above conditions A to C. Furthermore, Comparative Examples 1 to 18 did not satisfy some or all of the conditions of a residual magnetic flux density (Br) of 11.8 kG or more, a coercive force (Hcj) of 20 kOe, and a squareness ratio (Hk / Hcj) of 65% or more.
[0094] While the present invention has been described above with reference to the above-described embodiment, the present invention is not limited to the configuration of the above-described embodiment, and of course includes various modifications, alterations, and combinations that may be made by a person skilled in the art within the scope of the invention as defined in the claims of the present application. [Explanation of symbols]
[0095] 10 Grains 11 2-17 phase 12 1-5 phase 20 Grain boundary phase 100 Rare Earth Cobalt Permanent Magnets
Claims
1. A sintered body having a composition containing R: 24 to 27 wt% (where R is a total of rare earth elements including at least Sm), Fe: 23 to 27 wt%, Cu: 4.0 to 5.0 wt%, Zr: 1.5 to 2.5 wt%, Mn: 0.1 to 2.5 wt%, and the balance being Co and unavoidable impurities, The alloy has a plurality of crystal grains and a grain boundary phase, and an average Mn concentration in the grain boundary phase is 0.5 to 1.5 times the average Mn concentration in the crystal grains; The crystal grains are 2 Zinc 17 2-17 phase and RCo of type structure 5 and a 1-5 phase having a 2-17 phase structure, wherein the average Mn concentration in the 1-5 phase is 0.4 to 1.5 times the average Mn concentration in the 2-17 phase. Rare earth cobalt permanent magnet.
2. 2. The rare earth-cobalt permanent magnet of claim 1, wherein the average concentrations of Cu and Zr in the grain boundary phase are at least two times higher than the average concentrations of Cu and Zr in the crystal grains.
3. 3. The rare earth-cobalt permanent magnet according to claim 1, wherein the average Mn concentration in the grain boundary phase is 0.8 to 1.2 times the average Mn concentration in the crystal grains.
4. 3. The rare earth-cobalt permanent magnet according to claim 1, wherein the average Mn concentration in the 1-5 phase is 0.8 to 1.0 times the average Mn concentration in the 2-17 phase.
5. 3. The rare earth-cobalt permanent magnet according to claim 1, wherein the average concentrations of Cu and Zr in the grain boundary phase are at least four times higher than the average concentrations of Cu and Zr in the crystal grains.
6. 3. The rare earth-cobalt permanent magnet according to claim 1, having a residual magnetic flux density (Br) of 11.8 kG or more.
7. 3. The rare earth-cobalt permanent magnet according to claim 1, having a coercive force (Hcj) of 20 kOe or more.
8. 3. The rare earth-cobalt permanent magnet according to claim 1, having a squareness ratio, expressed as the ratio (Hk / Hcj) of the magnetic field (Hk) to the coercive force (Hcj), of 65% or more.
9. A device comprising the rare earth cobalt permanent magnet according to claim 1 or 2.
10. a step (I) of preparing an ingot containing each of the raw materials so that after sintering, the ingot has a composition containing 24 to 27 wt% R (where R is the total of rare earth elements including at least Sm), 23 to 27 wt% Fe, 4.0 to 5.0 wt% Cu, 1.5 to 2.5 wt% Zr, 0.1 to 2.5 wt% Mn, with the balance being Co and unavoidable impurities; A crushing step (II) of crushing the ingot into powder; A pressure molding step (III) of forming the powder into a molded body; A sintering step (IV) of heating the molded body to form a sintered body; a solution treatment step (V) of heating the sintered body to perform a solution treatment; a quenching step (VI) of quenching the sintered body after the solution treatment step (V); Th 2 Zinc 17 2-17 phase and RCo of type structure 5 and an aging treatment step (VII) for forming the 1-5 phase of the type structure, The step (I) of preparing an ingot comprises: a first ingot heat treatment step of treating the mixture of the raw materials at a first ingot heat treatment temperature; a second ingot heat treatment step of treating the mixture at a second ingot heat treatment temperature after the first ingot heat treatment step; When the sintering temperature of the molded body is S1 and the temperature of the solution treatment is S2, The first ingot heat treatment temperature T1 satisfies S1-50≦T1≦S1 (however, when the temperature difference between S1 and S2 is within 50° C., S2<T1≦S1), The second ingot heat treatment temperature T2 satisfies S2-30≦T2≦S2; Manufacturing method of rare earth cobalt permanent magnet.
11. The heat treatment time of the first ingot heat treatment step is 0.5 hours or more and 3.0 hours or less, The heat treatment time of the second ingot heat treatment step is 1.0 hour or more and 10.0 hours or less. The method for producing the rare earth cobalt permanent magnet according to claim 10.
12. The sintering step (IV) is a step of heating the molded body at a temperature of 1170° C. or more and 1215° C. or less for 20 minutes or more and 210 minutes or less, The solution treatment step (V) is a step of heating the sintered body at 1110° C. or more and 1165° C. or less for 5 hours or more and 150 hours or less, The quenching step (VI) is a step of lowering the temperature at a cooling rate of 60 ° C. / min or more from the solution treatment temperature to 600 ° C. after the solution treatment step (V). The method for producing a rare earth-cobalt permanent magnet according to claim 10 or 11.
13. 12. The method for producing a rare earth-cobalt permanent magnet according to claim 10, wherein in the crushing step (II), the ingot is crushed so that the particle size D10 is less than 4 μm, the particle size D50 is 5 μm or more and 8 μm or less, and the particle size D90 is less than 16 μm.
14. the rare earth-cobalt permanent magnet has a plurality of crystal grains and a grain boundary phase, the average Mn concentration in the grain boundary phase being 0.5 to 1.5 times the average Mn concentration in the crystal grains; The crystal grains are 2 Zinc 17 2-17 phase and RCo of type structure 5 and a 1-5 phase having a 2-17 phase structure, wherein the average Mn concentration in the 1-5 phase is 0.4 to 1.5 times the average Mn concentration in the 2-17 phase. The method for producing a rare earth-cobalt permanent magnet according to claim 10 or 11.
Citation Information
Patent Citations
Permanent magnet, method of manufacturing the same, motor using the same, and generator
JP2012069750A
Permanent magnet, rotary electric machine, and vehicle
JP2017168827A
Rare earth cobalt permanent magnet and method for manufacturing the same, and device
JP2020188140A
Rare earth cobalt permanent magnet, method for manufacturing the same, and device
JP2021125678A
Permanent magnet and device
JP2023049543A